Data archive for exploring pedestrian dynamics and its application in dimensioning of facilities for multidirectional streams - Boltes, Maik; Holl, Stefan; Seyfried, Armin (Collective Dynamics, 2020)
In this paper an overview of an open data archive with data from experiments investigating pedestrian dynamics is presented. As an example of the use of this data the analysis of recently published data about the capacity of crossings is shown.